Three ways of conceptualizing the Global: the Universal, the Holistic and the Macrocosmic-Commentary Isham B. Pawan Ahmad, Malaysia, page 97-98 - Pawan Ahmad, Isham (Asia and Pacific Regional Bureau for Education, UNESCO Bangkok, 2011)
Commentary Isham B. Pawan Ahmad, Malaysia Philip Cam’s reexamination on the ways of conceptualizing the global from a philosophical perspective through analyzing three cognates with the global: the universal, the holistic and the macrocosmic is extremely thought provoking. Cam’s attempt to evaluate what most see as a contemporary economic development, globalization through the lenses of philosophy not only reconnects the global experiment to the development in human thought but also raises again the questions of the very foundations that form the basis of human concepts of right and wrong and the role the acceptance of Western concepts of human rights that has restricted other possible interpretations of human rights from even entering the debate. Is the Western metaphysical status of rights the only way to establish rights issues? Hadn’t this Western metaphysical status of rights undergone a progression of development before they became widely accepted and therefore should have been affected and bound by time and place limitations?